2015
DOI: 10.1007/s00018-015-1993-0
|View full text |Cite
|
Sign up to set email alerts
|

APP controls the formation of PI(3,5)P2 vesicles through its binding of the PIKfyve complex

Abstract: Phosphoinositides are signalling lipids that are crucial for major signalling events as well as established regulators of membrane trafficking. Control of endosomal sorting and endosomal homeostasis requires phosphatidylinositol-3-phosphate (PI(3)P) and phosphatidylinositol-3,5-bisphosphate (PI(3,5)P2), the latter a lipid of low abundance but significant physiological relevance. PI(3,5)P2 is formed by phosphorylation of PI(3)P by the PIKfyve complex which is crucial for maintaining endosomal homeostasis. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 53 publications
2
54
0
Order By: Relevance
“…In view of the interesting similarities between intracellular trafficking and processing of PMEL and amyloid precursor protein (APP), which is involved in Alzheimer's disease (Bissig et al, 2016;Sannerud et al, 2016), our studies may also have important implications for pathological amyloid formation during Alzheimer's disease. Intriguingly, PIKfyve depletion leads to massive neurodegeneration in individuals with mutations of FIG4 and VAC14 (Baulac et al, 2014;Campeau et al, 2013;Chow et al, 2007;Lenk et al, 2011;Lenk et al, 2016), and PIKfyve influences APP (Balklava et al, 2015;Currinn et al, 2016). It is therefore tempting to speculate that, in neurons, PIKfyve activity regulates the abundance of an amyloidogenic substrate and its proteases in a compartment known to generate the Aβ intracellular pool (Peric and Annaert, 2015;Rajendran and Annaert, 2012;Sannerud et al, 2016).…”
Section: Implications For Pathological Amyloid Formationmentioning
confidence: 99%
“…In view of the interesting similarities between intracellular trafficking and processing of PMEL and amyloid precursor protein (APP), which is involved in Alzheimer's disease (Bissig et al, 2016;Sannerud et al, 2016), our studies may also have important implications for pathological amyloid formation during Alzheimer's disease. Intriguingly, PIKfyve depletion leads to massive neurodegeneration in individuals with mutations of FIG4 and VAC14 (Baulac et al, 2014;Campeau et al, 2013;Chow et al, 2007;Lenk et al, 2011;Lenk et al, 2016), and PIKfyve influences APP (Balklava et al, 2015;Currinn et al, 2016). It is therefore tempting to speculate that, in neurons, PIKfyve activity regulates the abundance of an amyloidogenic substrate and its proteases in a compartment known to generate the Aβ intracellular pool (Peric and Annaert, 2015;Rajendran and Annaert, 2012;Sannerud et al, 2016).…”
Section: Implications For Pathological Amyloid Formationmentioning
confidence: 99%
“…PIKfyve was inhibited for a brief amount of time (46). While so far we have not been able to measure PI(3,5)P2 levels biochemically, all our cell biological findings suggest that APP gene family members modulate PIKfyve function.…”
Section: Moreover App and Aplp2 Joint Suppression Sensitised Cells Fmentioning
confidence: 61%
“…Using a novel PI(3,5)P2 specific probe (47) we showed that overexpression of APP or ACID increased the number of PI(3,5)P2 positive vesicles in both HeLa and SH-SY5Y neuroblastoma cells. Conversely, knock-down of APP or the APP paralogue APLP2 reduced the number of PI(3,5)P2 positive vesicles in HeLa cells, suggesting that APP and its paralogues APLP2 are both able to stimulate PIKfyve function (46). RNAi Suppression of APP and APLP2 also increased the number of cells that display vacuoles, similar to the phenotype observed with PIKfyve RNAi, although to a lower extent (22,46).…”
Section: The Amyloid Precursor Protein (App) Binds To and Regulates Pmentioning
confidence: 67%
See 1 more Smart Citation
“…Mutations in FIG4 were also found in Yunis‐Varon syndrome, a neurological disorder with skeletal defects and severe neuronal loss in the central nervous system (Nakajima et al, ), as well as in some forms of amyloid lateral sclerosis, although a causal link has not yet been proved (Chow et al, ). Last but not least and as discussed above, FIG4 is part of the PIKfyve complex, which has been shown to be regulated by APP and, thus, may play a role in Alzheimer's disease (Currinn et al, ; Currinn and Wassmer, ). Mutations in a different phosphoinositide phosphatase, MTM‐related 2 ( MTMR2 ), which dephosphorylates both PI(3,5)P 2 and PI(3)P at the third hydroxyl group, lead to another form of Charcot‐Marie‐Tooth disease, CMT4B1 (Bolino et al, ).…”
Section: Pten and Other Phosphoinositide Phosphatases In Autismmentioning
confidence: 94%